Science in the Forest, Science in the Past - Lloyd, Geoffrey E. R.; Vilaça, Aparecida (HAU Books, 2020)
This collection brings together leading anthropologists, historians, philosophers, and artificial-intelligence researchers to discuss the sciences and mathematics used in various Eastern, Western, and Indigenous societies, both ancient and contemporary. The authors analyze prevailing assumptions about these societies and propose more faithful, sensitive analyses of their ontological views about reality-a step toward mutual understanding and translatability across cultures and research fields.Science in the Forest, Science in the Past is a pioneering interdisciplinary exploration that will challenge the way readers interested in sciences, mathematics, humanities, social research, computer sciences, and education think about deeply held notions of what constitutes reality, how it is apprehended, and how to investigate it.